Fatigue and efficiency of prolonged cycling - Lepers, R. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Performance of prolonged cycling exercise depends on the ability to sustain the higher power output during the whole duration of exercise. In addition, due to the stochastic nature of the road races, the performance may also depend on the ability of cyclist to produce a maximal power output (sprint) until the end of the event. St Clair Gibson (2001) found that maximal power output declined parallel with decreases in IEMG activity of the rectus femoris muscle for repeat 1-km high intensity exercise bouts during a 100-km cycling time trial. The authors postulated that the progressive reduction in neuromuscular activity may be the cause of fatigue in this trial. Neuromuscular fatigue which is defined as exercise-induced reduction in maximal voluntary force has been evidenced after prolonged cycling exercise by numerous studies (for review see Millet and Lepers, 2004). Isometric strength loss of the knee extensor muscles following prolonged cycling varied from 5 to 35% depending of the duration and the intensity of the exercise ; the greater strength loss being observed after cycling exercises performed until exhaustion (figure 1). The development of central fatigue during prolonged cycling exercise has been frequently suggested in the past years but has only been evidenced by recent studies. Two techniques are frequently used to quantify central fatigue. The first method, named method of the twitch superimposition or interpolation, consists to compare a twitch superimposed to a maximal voluntary contraction (MVC) and a twitch evoked on the muscle relaxed. The second method consists to analyse the ratio of the root mean square (RMS) of the EMG signal during MVC divided by the M-wave amplitude or RMS. A reduction in the MVC RMS without a reduction of M-wave amplitude or RMSM may be interpreted as a central activation failure. These two techniques have been used on the knee extensor muscles throughout long duration cycling exercise during short interruptions of the exercise where subjects had to seat in an isometric ergometer. Nevertheless, with the techniques described above to estimate an activation deficit, it is not possible to determine whether the central fatigue originates from a supraspinal site an/or from the spinal level. Neurally mediated afferent feedback from the muscle (group III and IV afferent fibres) such as presynaptic inhibition or fusimotor system disfacilitation might play a part in the inhibition of motoneuron excitability at a spinal level. Previous studies also suggested that changes in concentration of serotonin in the brain during prolonged cycling exercise may play a role in supraspinal fatigue. In addition to estimate activation level, evoked contractions have been used to explore peripheral components such as neuromuscular propagation and excitation-contraction (EC) coupling process. It appears that M-wave characteristics of the vastii muscles are not always altered by prolonged cycling exercise. In contrast, twitch mechanical response decreased systematically after endurance cycling exercise that evidenced an alteration of EC coupling process. Several studies showed that both peripheral and central components of fatigue occurred following prolonged cycling exercise, but the time course of such impairments during long duration cycling exercise are still misunderstood. A recent study (Lepers et al., 2002) examined the impairment in central and peripheral processes during a long-duration 5-h cycling exercise performed at 55% of the maximal aerobic power. The findings demonstrated that a 5-h cycling exercise progressively reduced the maximal voluntary force-generating capacity in the quadriceps muscles. The time course was such that the excitation-contraction (EC) coupling process was significantly altered after the first hour, whereas excitability (M-wave) and central drive were more impaired towards the latter stages. In conclusion, recent works show that both peripheral and central components of fatigue contribute to strength loss and thus reduce efficiency during prolonged cycling exercises, but the peripheral and central processes of fatigue may have different timings.